Gender, sexuality and subjectivity : a Lacanian perspective on identity, language, and queer theory - Rousselle, Duane (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This thought-provoking new book offers a concise yet comprehensive introduction to American gender and sexuality theory. It aims to make an intervention into the contemporary American paradigm of gender and sexuality theory by fundamentally challenging the paradigm of social constructionism. There are unacknowledged truths within each of the scholarly paradigms on gender. The controversial claim of this book is that queer theory and intersectionality - and, more broadly, the social constructionist paradigm - have reached their limit. Indeed, it is possible that they are now regressive theories. However, it is possible to move forward into a new paradigm through a logic that Rousselle names 'gender invention.' Part of the popular Routledge Focus on Mental Health series, this book will be of immense value to students and teachers who aim to understand in a basic way some of various main paradigms, theories, and concepts within gender and sexuality studies. It will also be an important attempt to think beyond those paradigms and theories"--
Gender meta-theory: an in(ter)vention -- Theory as an antidote to chaos -- Thinking gender as a Marxist: foundational ideas -- The social construction of gender: the case of queer theory -- Situating paradigms: from intersectionality to citational practices -- Interrogating intersectionality -- Psychoanalysis & gender: the mobius strip -- Subject formations -- Trans* inventions: from anxiety to certainty.
OCLC-licensed vendor bibliographic record.
Keywords: Gender identity -- Psychological aspects; Sex -- Psychological perspectives; Queer theory; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health